The Moderating Role of Enterprise Risk Management on the Influence of Environmental Performance, Firm Size, and Managerial Ownership on Financial Performance: An Empirical Study in Indonesia - Triwibowo, Ari; Kurniasih, Augustina (International Journal of Social and Management Studies, 2025)
This study aims to examine the effects of environmental performance, firm size, and managerial ownership on the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX), and to analyze the moderating role of Enterprise Risk Management (ERM) in these relationships. A quantitative study with a causal design was employed, utilizing Moderated Regression Analysis (MRA) on panel data with the Fixed Effect Model (FEM).The research was conducted using secondary data obtained from the annual reports and sustainability reports of transportation and logistics companies listed on the IDX, covering the period from January 2021 to December 2024. The sample consisted of 30 transportation and logistics companies that met the sampling criteria. Financial performance was measured using Return on Assets (ROA), environmental performance using the GRI 300 disclosure index, firm size using the natural logarithm of total assets, managerial ownership as the percentage of shares held by management, and ERM using the COSO ERM 2017 disclosure index. Firm size and managerial ownership have a positive and significant effect on financial performance, while environmental performance shows a significant negative effect. ERM significantly strengthens the influence of environmental performance on financial performance but does not significantly moderate the effect of firm size. Furthermore, ERM negatively moderates the effect of managerial ownership on financial performance.